Method for estimating railroad track settlements due to dynamic traffic loads - Queiroz, Rudney C. [UNESP]; Macari, Emir José (My University, 2005)
This paper is the result of real-scale physical modeling study designed to simulate the load-deformation characteristics of railroad foundation systems that include the railroad ties, the ballast, and the sub-base layers of a railroad embankment. The study presents comparisons of the application of dynamic loads of 100kN on the rails, and the resulting deformations during a 500,000 cycle testing period for three rail support systems; wood, concrete and steel. The results show that the deformation curve has an exponential shape, with the larger portion of the deformation occurring during the first 50,000 load cycles followed by a tendency to stabilize between 100,000 to 500,000 cycles. These results indicate that the critical phase of deformations of a new railroad is within the first 50,000 cycles of loading, and after that, it slowly attenuates as it approaches a stable value. The paper also presents empirically derived formulations for the estimation of the deformations of the rail supports as a result of rail traffic.
Keywords: Cycle testing; Deformation curves; Dynamic traffic; Foundation systems; Load cycle; Load deformation; Physical modeling; Rail traffic; Sub-bases; Support systems; Track settlement; Concrete testing; Dynamic loads; Geotechnical engineering; Loading; Models; Railroads; Soil mechanics; Steel testing; Deformation